2013
DOI: 10.1002/mnfr.201300224
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics determine hypolipidemic and antioxidant effects in hyperlipidemic hamsters

Abstract: Our data support the administration of probiotics to humans because of their hypolipidemic (through decreasing intestinal NPC1L1 and MTTP) and antioxidant effects (stimulating HDL-associated paraoxonase-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 45 publications
4
40
0
Order By: Relevance
“…It remains unclear whether protection against IBD afforded by probiotics or antibiotics that alter the gut microbiota extend beyond the gut. This appears likely in view of reports describing beneficial effects of oral probiotic treatment in clinical and animal studies of arthritis and cardiovascular diseases, including myocardial infarction and atherosclerosis 2022 . The overall objective of this study was to determine whether the enhanced extra-intestinal thrombus development associated to experimental colitis (induced by dextran sodium sulfate) is altered by oral treatment with the probiotic preparation.…”
Section: Introductionmentioning
confidence: 92%
“…It remains unclear whether protection against IBD afforded by probiotics or antibiotics that alter the gut microbiota extend beyond the gut. This appears likely in view of reports describing beneficial effects of oral probiotic treatment in clinical and animal studies of arthritis and cardiovascular diseases, including myocardial infarction and atherosclerosis 2022 . The overall objective of this study was to determine whether the enhanced extra-intestinal thrombus development associated to experimental colitis (induced by dextran sodium sulfate) is altered by oral treatment with the probiotic preparation.…”
Section: Introductionmentioning
confidence: 92%
“…It is accepted that the oxidized apoAI is a marker of dysfunctional HDL . Our previous results show the presence of 4‐hydroxynonenal (4‐HNE) adducts in apoAI in HDL from HL hamsters plasma . PON1 is synthesized mainly by the liver ; however, PON1 distribution along the gastrointestinal tract in humans is under debate .…”
Section: Introductionmentioning
confidence: 99%
“…olive flounder (Paralichthys olivaceus;Hasan et al, 2019) and the common carp (Cyprinus carpio;Ghodratizadeh, Farhoudi, & Habibian, 2011) fed with probiotics. Additionally, previous studies suggested that probiotics served as hypolipidemic could improve lipid metabolism and reduce blood lipids(Stancu, Sanda, Deleanu, & Sima, 2014). Additionally, previous studies suggested that probiotics served as hypolipidemic could improve lipid metabolism and reduce blood lipids(Stancu, Sanda, Deleanu, & Sima, 2014).…”
mentioning
confidence: 99%